2023
DOI: 10.1001/jamanetworkopen.2023.9549
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Illicit Substances by Young Children Before and During the COVID-19 Pandemic

Abstract: ImportanceInformation about the trend in illicit substance ingestions among young children during the pandemic is limited.ObjectivesTo assess immediate and sustained changes in overall illicit substance ingestion rates among children younger than 6 years before and during the COVID-19 pandemic and to examine changes by substance type (amphetamines, benzodiazepines, cannabis, cocaine, ethanol, and opioids) while controlling for differing statewide medicinal and recreational cannabis legalization policies.Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…We analyzed the KYRBS data to investigate the national trends in hand and oral hygiene behaviors during the past 15 years in the context of before and after the pandemic. Interrupted time series analysis was performed using an ordinary least-squares model (linear regression), logistic regression, and estimate of adjusted odds ratio (OR) to investigate immediate and sustained changes in hand and oral hygiene behaviors before and during the pandemic . We conducted sex and age standardization and adjustment for sex, grade, BMI, current alcohol use, current smoking status, highest educational level of parents, household economic level, and school performance.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed the KYRBS data to investigate the national trends in hand and oral hygiene behaviors during the past 15 years in the context of before and after the pandemic. Interrupted time series analysis was performed using an ordinary least-squares model (linear regression), logistic regression, and estimate of adjusted odds ratio (OR) to investigate immediate and sustained changes in hand and oral hygiene behaviors before and during the pandemic . We conducted sex and age standardization and adjustment for sex, grade, BMI, current alcohol use, current smoking status, highest educational level of parents, household economic level, and school performance.…”
Section: Methodsmentioning
confidence: 99%
“…Children who reside in homes where adult drug use is occurring are at risk of accidentally ingesting those substances . Recent research indicates that there has been a 26% increase in illicit drug ingestions in children since the onset of COVID-19 and pediatric hospitalizations for cannabis poisoning has doubled in areas with recreational legalization . Young children often ingest these drugs through exploratory means as they are unaware of the dangers; caregivers who are using substances may be less able to monitor their children’s behavior …”
Section: Introductionmentioning
confidence: 99%
“…A previous study that examined drug exposure beyond the neonatal period using hospital data from 2006 to 2008 found that only 4% of cases were reported to CPS and reporting rates varied by substance type . Given increases in child ingestion rates, and the legalization of cannabis in many states, understanding both reporting practices and CPS responses by drug type when a child tests positive is important …”
Section: Introductionmentioning
confidence: 99%
“…This role is especially important now because the COVID-19 pandemic saw an increase in ingestion of illicit substances among young children. 10 Clinicians treat patients after unintentional exposures, including those resulting in hospitalizations. Clinicians also in-teract with patients and have the opportunity to discuss responsible cannabis use, namely keeping cannabis out of children's reach.…”
mentioning
confidence: 99%
“…Health care professionals are on the front line of this issue and play an invaluable role as educators of the potential dangers posed by unregulated, untested, and unlicensed cannabis that targets minors. This role is especially important now because the COVID-19 pandemic saw an increase in ingestion of illicit substances among young children . Clinicians treat patients after unintentional exposures, including those resulting in hospitalizations.…”
mentioning
confidence: 99%